2017
DOI: 10.1189/jlb.1ma0316-131r
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of CD103 (αE integrin) expression in human dendritic cells by retinoic acid and Toll-like receptor ligands

Abstract: CD103 (αE integrin) is an important dendritic cell (DC) marker that characterizes functionally distinct DC subsets in mice and humans. However, the mechanism by which CD103 expression is regulated in human DCs and the role of CD103 for DC function are not very well understood. Here, we show that retinoic acid (RA) treatment of human monocyte-derived DCs (MoDCs) increased the ability of the DCs to synthesize RA and induced MoDC expression of CD103 and β7 at the mRNA and protein level. In contrast, RA was unable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 54 publications
(114 reference statements)
4
62
2
Order By: Relevance
“…Previous studies reported that GM-CSF upregulates CD103 expression on BM-derived DCs differentiated with FLT3-L in vitro, and that GM-CSF or GM-CSF receptor deficient mice display altered CD103 expression on DC1s in several organs, including the lung [25,[28][29][30][31][32]. Interestingly, previous reports show that LPS blocks CD103 expression induced by retinoic acid on human monocyte derived-DCs [33]. Therefore, we hypothesised that LPS-induced inflammation could impact the GM-CSFinduced CD103 expression on DCs upon their final maturation in the lung, and/or induce systemic alterations of pre-DCs differentiation towards the XCR1 + /CD103 + DCs, contributing to altered CD103 + DC populations following LPS exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that GM-CSF upregulates CD103 expression on BM-derived DCs differentiated with FLT3-L in vitro, and that GM-CSF or GM-CSF receptor deficient mice display altered CD103 expression on DC1s in several organs, including the lung [25,[28][29][30][31][32]. Interestingly, previous reports show that LPS blocks CD103 expression induced by retinoic acid on human monocyte derived-DCs [33]. Therefore, we hypothesised that LPS-induced inflammation could impact the GM-CSFinduced CD103 expression on DCs upon their final maturation in the lung, and/or induce systemic alterations of pre-DCs differentiation towards the XCR1 + /CD103 + DCs, contributing to altered CD103 + DC populations following LPS exposure.…”
Section: Introductionmentioning
confidence: 99%
“…An additional factor in DC differentiation of Tregs is retinoic acid (RA). While RA enhanced expression of αE integrin (CD103) and mucosal homing receptor β7 in MoDCs, Roe et al . found no such effect on primary human gastric DCs, indicating strong influences of the mucosal environment.…”
Section: Immunologymentioning
confidence: 98%
“…21,23,27 Our previous analyses showed that RA signaling leading to CD103 expression in human DCs intersects with transforming growth factor-b (TGF-b) signaling, as a small molecule inhibitor of the TGF-b receptor prevented RA-induced CD103 up-regulation. 13 In activated CD8 T cells, TGF-b leads to strong induction of CD103 expression. 28,29 However, TGF-b alone does not drive CD103 expression in DCs, as we and others have shown, 13,17 pointing to complex interactions between RA signaling and TGF-b signaling pathways.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…[9][10][11] Importantly, a significant number of animal studies have revealed an association between DC production of RA, the DC response to RA and DC expression of CD103, the a-chain of integrin a E b 7 . 7,8,[12][13][14] CD103 is a functionally important subset marker for gastrointestinal DCs in mice and is also expressed on mucosal DC subsets in humans. 7,15,16 Analyses from our laboratory and others have demonstrated that RA drives the expression of CD103 (integrin a E ) as well as the corresponding b-chain integrin b 7 on human DCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation